Improving the Efficacy of Cisplatin using Niosome Nanoparticles Against Human Breast Cancer Cell Line BT-20 : An In Vitro Study - Kanaani, Leila; Mazloumi Tabrizi, Maral; Akbarzadeh Khiyavi, Azim; Javadi, Iraj (Asian Pacific Journal of Cancer Biology, 2017)
Objective: Today, cancer is one the most important challenges in modern medicine. Meanwhile, breast cancer is one of the most common causes of mortality among cancers. The initial response to the treatment and then becoming resistant to the cisplatin is one of basal challenges of treatment of breast cancer. Recently, using nanotechnology including drug nanocarrier named niosome can decrease adverse effects and increase the efficiency of treatment. Material and Methods: The aim of this research was to investigate using niosome nanoparticles containing cisplatin and investigation of their lethal effect on breast cancer cell line. Results: We found that using niosome nanoparticles can provide a suitable formulation of cisplatin drug. Conclusion: The efficiency of nanoniosome cisplatin was more than free drug, decreasing the administered dose and therefore the damage to other tissues.